A Study of the Worldview in the Mythology of the Dani Ethnic Group in Papua and Its Ethical Implications Through the Lens of Christian Perspective - Mawikere, Marde Christian Stenly; Hura, Sudiria; Mawikere, Jean Calvin Riedel; Mawikere, Daniella Beauty Melanesia (PT. Giat Konseling Nusantara, 2025)
This study investigates the interplay between Dani cultural values and Christian ethics, focusing on how contextual evangelism can be effectively implemented within the Dani community in Papua. Utilizing a qualitative approach with an ethnographic methodology, the research combines field observations and content analysis to explore the impact of traditional Dani beliefs, particularly those encapsulated in the Nabelan-Kabelan and Naruekul mythologies, on Christian ethics and practices. Field observations involve immersive engagement with the Dani people to understand their cultural practices and religious expressions, while content analysis of relevant literature provides a theoretical foundation for interpreting these practices within the context of Christian teachings. The findings reveal that traditional Dani beliefs present both challenges and opportunities for contextual evangelism, highlighting the need for a nuanced approach that respects cultural values while introducing Christian ethics. The study concludes with recommendations for effective evangelistic strategies that integrate cultural insights with biblical teachings to foster ethical transformation and spiritual growth within the Dani community.